Topiramate and other kainate receptor antagonists for depression: A systematic review of randomized controlled trials - Ahmad Shamabadi (Wiley, 2022)
Abstract Background Depression is a common disorder that affects patients' quality of life and incurs health system costs. Due to the resistance to treat depression, better understanding of neurophysiology was considered; one of the implications is the glutamatergic system. This study aims to systematically review clinical trials investigating the antidepressant effects of kainate receptor antagonists. Methods The study protocol was registered in PROSPERO (CRD42021213912). Scopus, ISI, Embase, PubMed, Cochrane Library, Google Scholar, and two trial registries were searched for randomized controlled trials on the effectiveness of topiramate, phenobarbital, and other ten barbiturates in depression. The difference with control groups in terms of changing depressive symptoms was the primary outcome. Results Nine trials were identified, in which 784 patients were studied. The efficacy of thiopental was comparable to that of imipramine, with fewer side effects. When administered with electroconvulsive therapy, it had fewer to similar effects and fewer side effects than ketamine. Both monotherapy and adjunctive therapy with topiramate were effective and tolerable in treating depressed patients. Phenobarbital had therapeutic effects compared to imipramine and amitriptyline with fewer side effects. Conclusion Regarding the glutamatergic hypothesis of depression and obtained promising results, further studies of kainate receptor antagonists in high‐quality trials are recommended. Given the high prevalence of depression in epileptic patients, more problems with its treatment, and the fact that the studied agents were anticonvulsants, it is recommended that future studies prioritize depressed‐epileptic patients.